Kegiatan Membaca Untuk Menumbuhkan Kecintaan Terhadap Buku Sejak Usia Dini: Indonesia - Aprianti, Neli; Husaen Sudrajat; Syamsul Hadi (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
Currently people are expected to have a high interest in reading. Books are a source of knowledge and knowledge that have existed for a long time and are easy to find. Many can read but do not love books. This is because they do not understand from what they read, even though from the books they read they will get a lot of knowledge. Reading activities in Sayang-Sayang Village, Cakranegara District, Mataram City are one of the activities that must be carried out conceptually in dealing with the crisis of children's love of books. Organizing a program of reading activities for the community aimed at early childhood which aims to provide experience from reading together so that children have a love of books and love to read. The role of the community (parents) is needed to motivate and awaken the spirit of loving books, especially early childhood as a foundation for loving books more, not only reading but also being able to understand what they have read and also being able to relate it to real-world experiences. With this community service activity, the role of parents as a community becomes more optimal in helping develop children's love of books. This reading activity is a participatory activity involving community members in Sayang- Sayang Village and academics who assist in the smooth running of the activity.